Clinical and Microbiologic Evaluation of Chronic Leg Ulcers: A Cross-sectional Study - Souza, Jessica Molina de [UNESP]; Vieira, Erica Cristina [UNESP]; Cortez, Tatiana M. [UNESP]; Mondelli, Alessandro Lia [UNESP]; Miot, Hélio Amante [UNESP]; Abbade, Luciana Patrícia Fernandes [UNESP] (Lippincott Williams & Wilkins, 2014)
OBJECTIVE: This study aimed at evaluating the flora and bacterial load of chronic leg ulcers (CLUs) according to the clinical judgment of colonization or infection.DESIGN: This was an analytical and cross-sectional study.SETTING: This study was conducted in an outpatient wound care unit in the Dermatology Department of the Botucatu School of Medicine-UNESP, Brazil.PARTICIPANTS: The participants were patients with CLUs who did not use systemic antibiotics.METHODS: The ulcers were clinically divided into 3 groups: ulcers with good granulation tissue (GGT), critical colonization (CC), and infection. Secretion was collected from a 1-cm(2) area using a swab and seeded by the semiquantitative method.OUTCOME MEASURES: The main outcome measures were genus and species of the bacteria found in the cultures and result of the semiquantitative culture correlating with the clinical diagnosis of GGT, CC, and infection.MAIN RESULTS: Seventy-seven ulcers were evaluated: 27 with GGT, 29 with CC, and 21 with infection. Gram-negative bacteria were most often found in all groups (81%): Pseudomonas aeruginosa, in granulation and colonized ulcers, and Proteus mirabilis, in infected ulcers. Ulcers from the infected group showed higher bacterial load.CONCLUSIONS: The flora of CLUs was predominantly constituted by gram-negative bacteria, and P aeruginosa was the most prevalent. The bacterial load of infected ulcers was higher as compared with the others, although some ulcers with GGT also presented a high load. The interpretation of microbiologic tests based on the swab techniques and even on semiquantitative analysis requires close clinical correlation.
Keywords: venous leg ulcers; microbiology; wound healing; wound care